KETEPATAN PEMBERIAN DIET DENGAN PENGETAHUAN PRAMUSAJI TERHADAP MUTU PELAYANAN INSTALASI GIZI RSUD LEUWILIANG - Rini Suryanti; Sarah Handayani (Universitas Respati Indonesia, 2023)
Background : RSUD Leuwiliang has 391 inpatient beds that servers must feed. The results of the accuracy of data on the accuracy of patient feeding at the Nutrition Installation of Leuwiliang Hospital in 2018 were 98.25%, 98.45% in 2019, 98.42% in 2020, and 98.80% in 2021. The indicators show that An error has occurred in administering the patient's diet. RSUD Leuwiliang has not yet achieved a minimum service standard of 100% for indicators of the accuracy of patient feeding. Based on the background above, the researcher will know more about the results of